2020
DOI: 10.3390/cancers12020327
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Beta-Blockers and ACE-Inhibitors in Breast Cancer Patients Receiving Adjuvant Trastuzumab-Based Therapy and Developing Mild Cardiac Toxicity: A Prospective Study

Abstract: Background: Angiotensin Converting Enzyme inhibitors (ACEis) and beta-blockers (BB) are suggested to prevent and treat trastuzumab-related cardiac toxicity. We performed a prospective clinical trial in women experiencing mild cardiac toxicity (MCT) while on adjuvant treatment with trastuzumab. Methods: MCT was defined as an asymptomatic absolute decrease in LVEF of ≥ 10 percentage units to >50%. Treatment consisted of enalapril 2.5 mg bid and carvedilol 3.75 mg bid, which were up-titrated to 10 mg bid for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Research into the link between the RAS and cancer has accelerated greatly over the past years due to the growing evidence of local RAS signaling being deregulated in pathological tissues and the prominent role for the angiotensin receptors in tissue remodeling. As a result of the effects of ACE and the RAS as a whole, numerous studies have shown the association between ACE function and metabolic diseases such as diabetes as well as various cancers such as pancreatic and breast cancer [ 105 , 106 , 107 ]. Thus, drugs used to target RAS might also prove effective against cancer.…”
Section: Key Entry Genes Of Sars-cov-2 and Human Cancers Includingmentioning
confidence: 99%
“…Research into the link between the RAS and cancer has accelerated greatly over the past years due to the growing evidence of local RAS signaling being deregulated in pathological tissues and the prominent role for the angiotensin receptors in tissue remodeling. As a result of the effects of ACE and the RAS as a whole, numerous studies have shown the association between ACE function and metabolic diseases such as diabetes as well as various cancers such as pancreatic and breast cancer [ 105 , 106 , 107 ]. Thus, drugs used to target RAS might also prove effective against cancer.…”
Section: Key Entry Genes Of Sars-cov-2 and Human Cancers Includingmentioning
confidence: 99%
“…Geuna et al demonstrated that patients post-trastuzumab treated with study drugs were able to achieve the same LVEF values of patients that did not develop cardiotoxicity. However, more large-scale inquiries must be carried out to verify these findings [60].…”
Section: Ace Inhibitors Angiotensin Receptor Blockers and Beta-blocmentioning
confidence: 99%